Who Decides the Household Budget? Bibliometric Insights into Intrahousehold Dynamics - Abraham Peeter Bongiovi Simangunsong; Feryanto Feryanto; Tunggul Halomoan Sinaga; Margareth Henrika; Muhammad Ramadhani Kesuma (Indo Publishing, 2026)
This study conducts a bibliometric analysis of intrahousehold financial management research, drawing on 135 journal articles indexed in Scopus. Using VOSviewer, the analysis maps co-authorship networks, country collaborations, and keyword co-occurrence patterns to reveal the intellectual and social structure of the field. Results show a concentrated co-authorship network led by a small group of researchers, primarily from Japanese institutions, and a country collaboration pattern centered on the United States with strong links to Japan and several developing countries. Keyword analysis identifies gender as the central organizing concept, connected to four distinct thematic clusters focused on resource allocation, bargaining processes, decision-making and financial literacy, and broader social outcomes such as poverty and gender equality. These findings indicate that contemporary scholarship emphasizes gender disparities and bargaining power within households, particularly in developing contexts, while behavioral and psychological dimensions remain less integrated. The study highlights opportunities to broaden theoretical perspectives and geographic scope to achieve more comprehensive understandings of household financial practices.